Shakespeare unchained. Hamlet [videorecording (DVD)] (Synergetic Distribution, 2024)
A refreshing viewpoint of Shakespeare's Hamlet which compare topical issues during Shakespeare's times, giving new context to the meaning of the characters and storyline.